The therapeutic potential of CFTR modulators for COPD and other airway diseases. (June 2017) - Solomon, George M; Fu, Lianwu; Rowe, Steven M; Collawn, James F
Highlights: Common airway diseases including COPD, asthma and non-CF bronchiectasis (NCFBE) share the common pathophysiologic feature of mucus obstruction. Acquired CFTR dysfunction is a potential overlapping mechanism to explain abnormal mucus clearance in these diseases. CFTR modulators have shown promise in CF and thus should be tested in diseases with acquired CFTR dysfunction. Early studies indicate safety and promise efficacy for the CFTR potentiator ivacaftor in COPD with chronic bronchitis. Abstract : Airways diseases, especially chronic obstructive pulmonary disease (COPD) and asthma, are common causes of morbidity and mortality worldwide. There is an ongoing unmet need for novel and effective therapies. There is an established pathophysiological link and phenotypic similarity between the chronic bronchitis phenotype of COPD and cystic fibrosis (CF). New evidence suggests that CFTR dysfunction may play a role in other common airways diseases such as COPD, non-atopic asthma and non-CF bronchiectasis. Newly approved and investigational drugs that target both mutant and wild-type CFTR channels have provided a new treatment opportunity addressing the mucus defect in pulmonary diseases that share the same pathophysiology with CF.